FRAVÆR AF VIDEN, VIDEN OM FRAVÆR: Magiske effekter i det postsocialistiske Mongoliet - Højer, Lars (Tidsskriftet Antropologi, 2006)
The fall of socialism has brought about a renewed engagement with magical objects and practices in Mongolia. However, many years of religious repression during the seventy years of socialist rule have led people to believe that their knowledge of religion, spirit powers and magical phenomena is insufficient at best. It is beyond doubt that much knowledge and many religious objects were lost during socialism, especially during the purges of the 1930s. Yet, rather than analysing people’s dealings with spirit powers and magic as based on insufficient knowledge, this article attends to the current lack of knowledge about such phenomena, as well as to the ‘absent knowledge’ manifest in the aesthetics of certain objects and acts, as a precondition for their efficacy as magical objects and practices. As such, it is argued that it is this lack of knowledge that has made the phenomena in question more, and not less, magical and powerful.